Preparation method of gradient porous material loaded noble metal catalyst

By using the loading method of gradient porous materials in noble metal catalysts, the problems of insufficient selectivity and efficiency of existing catalysts are solved, and a more efficient catalytic reaction is achieved.

CN119524889APending Publication Date: 2025-02-28SUZHOU BIDING NEW MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411615447.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing precious metal catalysts have problems of insufficient selectivity and efficiency in catalytic reactions, especially when facing strict environmental protection and process safety requirements.

Method used

The preparation method of a gradient porous material-supported precious metal catalyst is adopted to promote the reagent-guided active sites through the structure of the gradient pore size, and optimize the adsorption and desorption of reactants by Pt, thereby improving catalytic efficiency and selectivity.

Benefits of technology

The rate and efficiency of selecting hydrogenation performance are improved, the active site of the catalyst is increased, the adsorption and desorption properties of Pt are optimized, and the comprehensive performance of the catalyst is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132084880000081
    Figure BDA0005132084880000081
  • Figure BDA0005132084880000091
    Figure BDA0005132084880000091
Patent Text Reader

Abstract

The invention provides a preparation method of a gradient porous material loaded noble metal catalyst. The method comprises the following steps: preparing hydroxyapatite powder; the preparation method comprises the following steps: taking hydroxyapatite powder, adding absolute ethyl alcohol, performing ultrasonic dispersion to prepare a suspension, adding polyvinyl butyral, and stirring with a magnetic stirrer to uniformly disperse the polyvinyl butyral to form hydroxyapatite slurry; taking three kinds of Pt catalyst loaded polylactic acid / glycolic acid copolymer microspheres with different particle sizes, and laying the microspheres in a mold according to the particle sizes; pouring the hydroxyapatite slurry into a mold, applying a certain pressure to fill gaps of microspheres with the hydroxyapatite slurry, and completely drying; and sintering in a sintering furnace to obtain the gradient porous material loaded noble metal catalyst. According to the invention, the noble metal catalyst is loaded on the gradient porous material, and the gradient aperture structure can promote the reactants to be guided by the capillary tube and quickly transfer the mass to each active site, so that the rate and efficiency of the selective hydrogenation performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalysts, and in particular to a method for preparing a gradient porous material-loaded noble metal catalyst. Background Art

[0002] Precious metal catalysts are an indispensable raw material in the process of chemical synthesis and are widely used in the synthetic pharmaceutical industry, new materials and fine chemicals. Especially in the face of increasingly stringent environmental protection and process safety requirements, precious metal catalysts have high selectivity and relatively low reaction conditions. At the same time, they have high value, which requires precious metal catalysts to be recycled. Therefore, on the one hand, they have become necessary catalysts in more and more customized syntheses. On the other hand, precious metal catalysts are constantly replacing some highly polluting non-ferrous metal catalysts (such as iron, nickel, and mercury catalysts) and are being used more and more widely.

[0003] Precious metal catalysts are precious metal materials that can change the speed of chemical reactions without participating in the final product of the reaction. Almost all precious metals can be used as catalysts, but platinum, palladium, rhodium, silver, ruthenium, etc. are commonly used, among which platinum (Pt) is the most widely used. Its d electron orbits are not filled, and the surface is easy to adsorb reactants with moderate strength, which is conducive to the formation of intermediate "active compounds". It has high catalytic activity and also has comprehensive excellent properties such as high temperature resistance, oxidation resistance, and corrosion resistance, making it the most important catalyst material.

[0004] According to the type of catalytic reaction, precious metal catalysts can be divided into two categories: homogeneous catalysis and heterogeneous catalysis. Catalysts for homogeneous catalysis are usually soluble compounds (salts or complexes), such as palladium chloride, rhodium chloride, palladium acetate, carbonyl rhodium, triphenylphosphine rhodium chloride, etc. Catalysts for heterogeneous catalysis are insoluble solids, and their main form is a porous inorganic carrier loaded with metal, such as Pt / A12O3, Pd / C, Ag / Al2O3, Rh / SiO2, Pt-Pd / Al2O3, Pt-Rh / Al2O3, etc. In the entire catalytic reaction process, heterogeneous catalytic reactions account for 80% to 90%. According to the shape of the carrier, the supported catalyst can be divided into microparticles, spheres, columns and honeycombs. There are no reports of gradient porous materials loaded with precious metal catalysts. Summary of the invention

[0003] Technical problem to be solved: The purpose of the present invention is to provide a method for preparing a gradient porous material loaded with precious metal catalysts. The gradient porous material is used to load the precious metal catalyst. The gradient pore size structure can promote the reactants to be guided by capillaries and quickly transfer mass to each active site, thereby improving the rate and efficiency of selective hydrogenation performance; at the same time, the pore size and pore structure of the gradient porous material can be regulated, which can optimize the adsorption and desorption of Pt on reactants, thereby improving the catalytic efficiency and selectivity.

[0004] Technical solution: A method for preparing a gradient porous material loaded with a noble metal catalyst, in parts by weight, comprises the following steps: S1: Take 0.25 mol / L H3PO4 solution, add ammonia water to adjust the pH of the solution, slowly add 1 mol / L CaCl2 solution, and control the pH of the solution to be constant, and continue stirring for 30 minutes; S2: aging for 24-72h, centrifuging, repeatedly washing until there is no ammonia smell, drying at 80-100℃, grinding through a 400-mesh sieve to obtain hydroxyapatite powder; S3: Take hydroxyapatite powder, add anhydrous ethanol, use ultrasonic dispersion to prepare a suspension, add 1% polyvinyl butyral by volume of the suspension, stir with a magnetic stirrer to make it evenly dispersed to form a hydroxyapatite slurry; S4: Take three different sizes of Pt catalyst-loaded polylactic acid / glycolic acid copolymer microspheres, and lay them flat in a mold according to the particle size, with the bottom particle size being larger and the top particle size being smaller, with a height of 1:1.5:(1-2); S5: pour the hydroxyapatite slurry into the mold of S4, apply a certain pressure to make the hydroxyapatite slurry fill the gaps between the microspheres, and dry it completely in an oven at 80°C; S6: Place the material in a sintering furnace for sintering, raise the temperature to 400-600°C for debinding, continue to raise the temperature to 1100-1250°C, and keep the temperature for 2 hours to obtain a gradient porous material loaded with a precious metal catalyst. Furthermore, in the S1, Ca / P=1.67-2.0, and the pH of the solution is adjusted to 9-11. Furthermore, the solid-liquid ratio of the hydroxyapatite powder and anhydrous ethanol in S3 is 1 g:2 mL. Furthermore, the particle sizes of the three different particle sizes of the polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst in S4 are 50-500 nm, 1-20 μm and 100-300 μm respectively. Furthermore, the specific preparation method of the polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst in S4 is as follows: S41: PVA is dissolved in a PBS solution to obtain 10 parts of a 1% PVA solution by mass, 2 parts of a chloroplatinic acid solution are added, and the mixture is stirred and allowed to stand at room temperature to serve as an aqueous phase; S42: 0.1 parts of PLGA are dissolved in 1 part of a dichloromethane / methanol mixed solvent as the oil phase; S43: adding the oil phase dropwise to the water phase under stirring at a speed of 160-180 rpm, stirring for 3 minutes to obtain a primary emulsion, then quickly taking it out, and homogenizing it at different speeds for 3-5 minutes to obtain final emulsions with different particle sizes; S44: adding an excess amount of sodium borohydride solution for reduction, stirring at 600 rpm for 2 h, and volatilizing the organic solvent to obtain solidified microspheres; S45: centrifuging at a rotation speed of 3000 rpm, washing with deionized water, and freeze-drying to obtain polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst. Furthermore, the mass fraction of platinum in the potassium chloroplatinate solution is 5-10%. Furthermore, the volume ratio of dichloromethane to methanol in the dichloromethane / methanol mixed solvent is 9:1. Furthermore, the different speeds in S43 are 30000rpm, 15000rpm, 7000-8000rpm, respectively, and finally obtain polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst with particle sizes of 50-500nm, 1-20μm and 100-300μm. The gradient porous material prepared by the above preparation method loads precious metal catalyst. Beneficial effects: 1. The present invention adopts gradient porous materials to load precious metal catalysts. The gradient pore size structure can promote the reactants to be guided by capillaries and quickly transfer mass to each active site, thereby improving the rate and efficiency of selective hydrogenation performance; at the same time, the pore size and pore structure of the gradient porous material can be regulated, which can optimize the adsorption and desorption of Pt on reactants, thereby improving the catalytic efficiency and selectivity. 2. The gradient porous material of the present invention has a large number of internal pores, and the specific surface area is greatly increased, which can provide a large number of active sites and help improve the activity of the catalyst. 3. The present invention uses hydroxyapatite to load Pt, which has excellent thermal stability and chemical stability, making its application range wider. DETAILED DESCRIPTION Example 1 The specific preparation method of polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst is as follows: S41: PVA is dissolved in a PBS solution to obtain 10 parts of a 1% PVA solution by mass, 2 parts of an 8% chloroplatinic acid solution by mass are added, and the mixture is stirred and allowed to stand at room temperature to serve as an aqueous phase; S42: taking 0.1 parts of PLGA and dissolving it in 1 part of a dichloromethane / methanol mixed solvent, wherein the volume ratio of dichloromethane to methanol in the dichloromethane / methanol mixed solvent is 9:1, as the oil phase; S43: adding the oil phase dropwise to the water phase under stirring at a speed of 170 rpm, stirring for 3 min to obtain a primary emulsion, then quickly taking it out, and homogenizing it at a speed of 30,000 rpm for 4 min to obtain a final emulsion; S44: adding an excess amount of sodium borohydride solution for reduction, stirring at 600 rpm for 2 h, and volatilizing the organic solvent to obtain solidified microspheres; S45: centrifuging at a rotation speed of 3000 rpm, washing with deionized water, and freeze-drying to obtain polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst. The particle size of the obtained microspheres is 50-500 nm. Example 2 The specific preparation method of polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst is as follows: S41: PVA is dissolved in a PBS solution to obtain 10 parts of a 1% PVA solution by mass, 2 parts of an 8% chloroplatinic acid solution are added, and the mixture is stirred and allowed to stand at room temperature to serve as an aqueous phase; S42: taking 0.1 parts of PLGA and dissolving it in 1 part of a dichloromethane / methanol mixed solvent, wherein the volume ratio of dichloromethane to methanol in the dichloromethane / methanol mixed solvent is 9:1, as the oil phase; S43: adding the oil phase dropwise to the water phase under stirring at a speed of 170 rpm, stirring for 3 min to obtain a primary emulsion, then quickly taking it out, and homogenizing it at a speed of 15000 rpm for 4 min to obtain a final emulsion; S44: adding an excess amount of sodium borohydride solution for reduction, stirring at 600 rpm for 2 h, and volatilizing the organic solvent to obtain solidified microspheres; S45: centrifuging at a rotation speed of 3000 rpm, washing with deionized water, and freeze-drying to obtain polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst. The obtained microspheres have a particle size of 1-20 μm. Example 3 The specific preparation method of polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst is as follows: S41: PVA is dissolved in a PBS solution to obtain 10 parts of a 1% PVA solution by mass, 2 parts of an 8% chloroplatinic acid solution are added, and the mixture is stirred and allowed to stand at room temperature to serve as an aqueous phase; S42: taking 0.1 parts of PLGA and dissolving it in 1 part of a dichloromethane / methanol mixed solvent, wherein the volume ratio of dichloromethane to methanol in the dichloromethane / methanol mixed solvent is 9:1, as the oil phase; S43: adding the oil phase dropwise to the water phase under stirring at a speed of 170 rpm, stirring for 3 min to obtain a primary emulsion, then quickly taking it out, and homogenizing it at a speed of 7500 rpm for 4 min to obtain a final emulsion; S44: adding an excess amount of sodium borohydride solution for reduction, stirring at 600 rpm for 2 h, and volatilizing the organic solvent to obtain solidified microspheres; S45: centrifuging at a rotation speed of 3000 rpm, washing with deionized water, and freeze-drying to obtain polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst. The particle size of the obtained microspheres is 100-500 nm. Example 4 The specific preparation method of polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst is as follows: S41: PVA is dissolved in a PBS solution to obtain 10 parts of a 1% PVA solution by mass, 2 parts of a 5% chloroplatinic acid solution by mass are added, and the mixture is stirred and allowed to stand at room temperature to serve as an aqueous phase; S42: taking 0.1 parts of PLGA and dissolving it in 1 part of a dichloromethane / methanol mixed solvent, wherein the volume ratio of dichloromethane to methanol in the dichloromethane / methanol mixed solvent is 9:1, as the oil phase; S43: adding the oil phase dropwise to the water phase under stirring at a speed of 160 rpm, stirring for 3 min to obtain a primary emulsion, then quickly taking it out, and homogenizing it at a speed of 30,000 rpm for 3 min to obtain a final emulsion with different particle sizes; S44: adding an excess amount of sodium borohydride solution for reduction, stirring at 600 rpm for 2 h, and volatilizing the organic solvent to obtain solidified microspheres; S45: centrifuging at a rotation speed of 3000 rpm, washing with deionized water, and freeze-drying to obtain polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst. The particle size of the obtained microspheres is 100-300 nm. Example 5 The specific preparation method of polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst is as follows: S41: PVA is dissolved in a PBS solution to obtain 10 parts by mass of a 1% PVA solution, 2 parts by mass of a 10% chloroplatinic acid solution are added, and the mixture is stirred and allowed to stand at room temperature to serve as an aqueous phase; S42: taking 0.1 parts of PLGA and dissolving it in 1 part of a dichloromethane / methanol mixed solvent, wherein the volume ratio of dichloromethane to methanol in the dichloromethane / methanol mixed solvent is 9:1, as the oil phase; S43: adding the oil phase dropwise to the water phase under stirring at a speed of 180 rpm, stirring for 3 min to obtain a primary emulsion, then quickly taking it out, and homogenizing it at a speed of 8000 rpm for 5 min to obtain a final emulsion with different particle sizes; S44: adding an excess amount of sodium borohydride solution for reduction, stirring at 600 rpm for 2 h, and volatilizing the organic solvent to obtain solidified microspheres; S45: centrifuging at a rotation speed of 3000 rpm, washing with deionized water, and freeze-drying to obtain polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst. The particle size of the obtained microspheres is 100-300 μm. The Pt loading amount of the polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst in each embodiment was measured, and the results are shown in Table 1 below: Table 1 Pt loading (mmol / g) Example 1 5.6 Example 2 5.2 Example 3 5.0 Example 4 5.5 Example 5 5.1 The microspheres with a particle size of 50-500 nm prepared in Example 1, the microspheres with a particle size of 1-20 μm prepared in Example 2, and the microspheres with a particle size of 100-300 μm prepared in Example 5 were selected. Example 6 A method for preparing a gradient porous material loaded with a noble metal catalyst comprises the following steps, measured in parts by weight: S1: Take 0.25 mol / L H3PO4 solution, add ammonia water to adjust the solution pH to 10, slowly add 1 mol / L CaCl2 solution, Ca / P = 1.67, and control the solution pH constant, continue stirring for 30 minutes; S2: aging for 24 hours, centrifuging, repeatedly washing until there is no ammonia smell, drying at 100°C, grinding through a 400-mesh sieve to obtain hydroxyapatite powder; S3: Take hydroxyapatite powder, add anhydrous ethanol, the solid-liquid ratio of hydroxyapatite powder and anhydrous ethanol is 1g:2mL, use ultrasonic dispersion to prepare a suspension, add 1% polyvinyl butyral by volume of the suspension, and stir with a magnetic stirrer to evenly disperse it to form a hydroxyapatite slurry; S4: Take three different sizes of Pt catalyst-loaded polylactic acid / glycolic acid copolymer microspheres, and lay them flat in the mold according to the particle size, with the bottom particle size being large and the top particle size being small, with a height ratio of 1:1.5:1; S5: pour the hydroxyapatite slurry into the mold of S4, apply a certain pressure to make the hydroxyapatite slurry fill the gaps between the microspheres, and dry it completely in an oven at 80°C; S6: Place the material in a sintering furnace for sintering, raise the temperature to 500°C for debinding, continue to raise the temperature to 1200°C, and keep the temperature for 2 hours to obtain a gradient porous material loaded with precious metal catalysts. Example 7 A method for preparing a gradient porous material loaded with a noble metal catalyst comprises the following steps, measured in parts by weight: S1: Take 0.25 mol / L H3PO4 solution, add ammonia water to adjust the solution pH to 10, slowly add 1 mol / L CaCl2 solution, Ca / P = 1.67, and control the solution pH constant, continue stirring for 30 minutes; S2: aging for 24 hours, centrifuging, repeatedly washing until there is no ammonia smell, drying at 100°C, grinding through a 400-mesh sieve to obtain hydroxyapatite powder; S3: Take hydroxyapatite powder, add anhydrous ethanol, the solid-liquid ratio of hydroxyapatite powder and anhydrous ethanol is 1g:2mL, use ultrasonic dispersion to prepare a suspension, add 1% polyvinyl butyral by volume of the suspension, and stir with a magnetic stirrer to evenly disperse it to form a hydroxyapatite slurry; S4: Take three different sizes of Pt catalyst-loaded polylactic acid / glycolic acid copolymer microspheres, and lay them flat in the mold according to the particle size, with the bottom particle size being large and the top particle size being small, with the height ratio of 1:1.5:1.5; S5: pour the hydroxyapatite slurry into the mold of S4, apply a certain pressure to make the hydroxyapatite slurry fill the gaps between the microspheres, and dry it completely in an oven at 80°C; S6: Place the material in a sintering furnace for sintering, raise the temperature to 500°C for debinding, continue to raise the temperature to 1200°C, and keep the temperature for 2 hours to obtain a gradient porous material loaded with precious metal catalysts. Example 8 A method for preparing a gradient porous material loaded with a noble metal catalyst comprises the following steps, measured in parts by weight: S1: Take 0.25 mol / L H3PO4 solution, add ammonia water to adjust the solution pH to 10, slowly add 1 mol / L CaCl2 solution, Ca / P = 1.67, and control the solution pH constant, continue stirring for 30 minutes; S2: aging for 24 hours, centrifuging, repeatedly washing until there is no ammonia smell, drying at 100°C, grinding through a 400-mesh sieve to obtain hydroxyapatite powder; S3: Take hydroxyapatite powder, add anhydrous ethanol, the solid-liquid ratio of hydroxyapatite powder and anhydrous ethanol is 1g:2mL, use ultrasonic dispersion to prepare a suspension, add 1% polyvinyl butyral by volume of the suspension, and stir with a magnetic stirrer to evenly disperse it to form a hydroxyapatite slurry; S4: Take three different sizes of Pt catalyst-loaded polylactic acid / glycolic acid copolymer microspheres, and lay them flat in the mold according to the particle size, with the bottom particle size being large and the top particle size being small, with a height ratio of 1:1.5:2; S5: pour the hydroxyapatite slurry into the mold of S4, apply a certain pressure to make the hydroxyapatite slurry fill the gaps between the microspheres, and dry it completely in an oven at 80°C; S6: Place the material in a sintering furnace for sintering, raise the temperature to 500°C for debinding, continue to raise the temperature to 1200°C, and keep the temperature for 2 hours to obtain a gradient porous material loaded with precious metal catalysts. Comparative Example 1 The difference between this embodiment and embodiment 7 is that all microspheres with a particle size of 50-500 nm prepared in embodiment 1 are used, as follows: A method for preparing a gradient porous material loaded with a noble metal catalyst comprises the following steps, measured in parts by weight: S1: Take 0.25 mol / L H3PO4 solution, add ammonia water to adjust the solution pH to 10, slowly add 1 mol / L CaCl2 solution, Ca / P = 1.67, and control the solution pH constant, continue stirring for 30 minutes; S2: aging for 24 hours, centrifuging, repeatedly washing until there is no ammonia smell, drying at 100°C, grinding through a 400-mesh sieve to obtain hydroxyapatite powder; S3: Take hydroxyapatite powder, add anhydrous ethanol, the solid-liquid ratio of hydroxyapatite powder and anhydrous ethanol is 1g:2mL, use ultrasonic dispersion to prepare a suspension, add 1% polyvinyl butyral by volume of the suspension, and stir with a magnetic stirrer to evenly disperse it to form a hydroxyapatite slurry; S4: Take the polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst and spread them flat in the mold; S5: pour the hydroxyapatite slurry into the mold of S4, apply a certain pressure to make the hydroxyapatite slurry fill the gaps between the microspheres, and dry it completely in an oven at 80°C; S6: Place the material in a sintering furnace for sintering, raise the temperature to 500°C for debinding, continue to raise the temperature to 1200°C, and keep the temperature for 2 hours to obtain a gradient porous material loaded with precious metal catalysts. Comparative Example 2 The difference between this embodiment and embodiment 7 is that all microspheres with a particle size of 1-20 μm prepared in embodiment 2 are used, as follows: A method for preparing a gradient porous material loaded with a noble metal catalyst comprises the following steps, measured in parts by weight: S1: Take 0.25 mol / L H3PO4 solution, add ammonia water to adjust the solution pH to 10, slowly add 1 mol / L CaCl2 solution, Ca / P = 1.67, and control the solution pH constant, continue stirring for 30 minutes; S2: aging for 24 hours, centrifuging, repeatedly washing until there is no ammonia smell, drying at 100°C, grinding through a 400-mesh sieve to obtain hydroxyapatite powder; S3: Take hydroxyapatite powder, add anhydrous ethanol, the solid-liquid ratio of hydroxyapatite powder and anhydrous ethanol is 1g:2mL, use ultrasonic dispersion to prepare a suspension, add 1% polyvinyl butyral by volume of the suspension, and stir with a magnetic stirrer to evenly disperse it to form a hydroxyapatite slurry; S4: Take the polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst and spread them flat in the mold; S5: pour the hydroxyapatite slurry into the mold of S4, apply a certain pressure to make the hydroxyapatite slurry fill the gaps between the microspheres, and dry it completely in an oven at 80°C; S6: Place the material in a sintering furnace for sintering, raise the temperature to 500°C for debinding, continue to raise the temperature to 1200°C, and keep the temperature for 2 hours to obtain a gradient porous material loaded with precious metal catalysts. Comparative Example 3 The difference between this embodiment and embodiment 7 is that all microspheres with a particle size of 100-300 μm prepared in embodiment 5 are used, as follows: A method for preparing a gradient porous material loaded with a noble metal catalyst comprises the following steps, measured in parts by weight: S1: Take 0.25 mol / L H3PO4 solution, add ammonia water to adjust the solution pH to 10, slowly add 1 mol / L CaCl2 solution, Ca / P = 1.67, and control the solution pH constant, continue stirring for 30 minutes; S2: aging for 24 hours, centrifuging, repeatedly washing until there is no ammonia smell, drying at 100°C, grinding through a 400-mesh sieve to obtain hydroxyapatite powder; S3: Take hydroxyapatite powder, add anhydrous ethanol, the solid-liquid ratio of hydroxyapatite powder and anhydrous ethanol is 1g:2mL, use ultrasonic dispersion to prepare a suspension, add 1% polyvinyl butyral by volume of the suspension, and stir with a magnetic stirrer to evenly disperse it to form a hydroxyapatite slurry; S4: Take the polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst and spread them flat in the mold; S5: pour the hydroxyapatite slurry into the mold of S4, apply a certain pressure to make the hydroxyapatite slurry fill the gaps between the microspheres, and dry it completely in an oven at 80°C; S6: Place the material in a sintering furnace for sintering, raise the temperature to 500°C for debinding, continue to raise the temperature to 1200°C, and keep the temperature for 2 hours to obtain a gradient porous material loaded with precious metal catalysts. The selective hydrogenation performance of the gradient porous material-supported noble metal catalyst of each embodiment was measured, and the results are shown in Table 2 below: Table 2

Claims

1. A method for preparing a gradient porous material loaded with a noble metal catalyst, characterized in that: By weight, the method comprises the following steps: S1: Take 0.25 mol / L H3PO4 solution, add ammonia water to adjust the pH of the solution, slowly add 1 mol / L CaCl2 solution, and control the pH of the solution to be constant, and continue stirring for 30 minutes; S2: aging for 24-72h, centrifuging, repeatedly washing until there is no ammonia smell, drying at 80-100℃, grinding through a 400-mesh sieve to obtain hydroxyapatite powder; S3: Take hydroxyapatite powder, add anhydrous ethanol, use ultrasonic dispersion to prepare a suspension, add 1% polyvinyl butyral by volume of the suspension, stir with a magnetic stirrer to make it evenly dispersed to form a hydroxyapatite slurry; S4: Take three different sizes of Pt catalyst-loaded polylactic acid / glycolic acid copolymer microspheres, and lay them flat in a mold according to the particle size, with the bottom particle size being larger and the top particle size being smaller, with a height of 1:1.5:(1-2); S5: pour the hydroxyapatite slurry into the mold of S4, apply a certain pressure to make the hydroxyapatite slurry fill the gaps between the microspheres, and dry it completely in an oven at 80°C; S6: Place the material in a sintering furnace for sintering, raise the temperature to 400-600°C for debinding, continue to raise the temperature to 1100-1250°C, and keep the temperature for 2 hours to obtain a gradient porous material loaded with a precious metal catalyst.

2. The method for preparing a gradient porous material-supported noble metal catalyst according to claim 1, characterized in that: The Ca / P in the S1 is 1.67-2.0, and the pH of the solution is adjusted to 9-11.

3. The method for preparing a gradient porous material-supported noble metal catalyst according to claim 1, characterized in that: The solid-to-liquid ratio of the hydroxyapatite powder and anhydrous ethanol in S3 is 1 g:2 mL.

4. The method for preparing a gradient porous material-supported noble metal catalyst according to claim 1, characterized in that: The particle sizes of the three different particle sizes of polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst in S4 are 50-500 nm, 1-20 μm and 100-300 μm respectively.

5. The method for preparing a gradient porous material-supported noble metal catalyst according to claim 1, characterized in that: The specific preparation method of the polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst in S4 is as follows: S41: PVA is dissolved in a PBS solution to obtain 10 parts of a 1% PVA solution by mass, 2 parts of a chloroplatinic acid solution are added, and the mixture is stirred and allowed to stand at room temperature to serve as an aqueous phase; S42: 0.1 parts of PLGA are dissolved in 1 part of a dichloromethane / methanol mixed solvent as the oil phase; S43: adding the oil phase dropwise to the water phase under stirring at a speed of 160-180 rpm, stirring for 3 minutes to obtain a primary emulsion, then quickly taking it out, and homogenizing it at different speeds for 3-5 minutes to obtain final emulsions with different particle sizes; S44: adding an excess amount of sodium borohydride solution for reduction, stirring at 600 rpm for 2 h, and volatilizing the organic solvent to obtain solidified microspheres; S45: centrifuging at a rotation speed of 3000 rpm, washing with deionized water, and freeze-drying to obtain polylactic acid / glycolic acid copolymer microspheres loaded with Pt catalyst.

6. The method for preparing a gradient porous material-supported noble metal catalyst according to claim 5, characterized in that: The mass fraction of platinum in the potassium chloroplatinate solution is 5-10%.

7. The method for preparing a gradient porous material-supported noble metal catalyst according to claim 5, characterized in that: The volume ratio of dichloromethane to methanol in the dichloromethane / methanol mixed solvent is 9:

1.

8. The method for preparing a gradient porous material-supported noble metal catalyst according to claim 5, characterized in that: The different speeds in S43 are 30000 rpm, 15000 rpm, and 7000-8000 rpm, respectively, and finally obtain Pt catalyst-loaded polylactic acid / glycolic acid copolymer microspheres with particle sizes of 50-500 nm, 1-20 μm, and 100-300 μm.

9. A gradient porous material loaded with a noble metal catalyst prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Cited By

  • Preparation method of continuous gradient stainless steel porous filtering material

    CN120243940A